Upaya Pencegahan Kekambuhan Asma Pada Anak - Nurul Fajri, Annisa; , Endang Zulaicha Susilaningsih, S.Kp., M.Kep; , Dian Nur Wulanningrum S.Kep., Ns., M.Kep (2017)
Background:Asthma is a chronic disease most often found in children. Increase prevalence the incidence of asthma relapse in Central Java for ages 5 to 14 years amounted 3,9%. Asthma relapse in children can be bad as having trouble sleeping at night wheezing, decreased daily activity and to the familycan be decreased to family members.Purpose: The purpose of writing this scientific papers is to do prevention relapse asthma on children in accordance with the nursing procedure. Methods:Method in use this scientific papers that is depcriptive method with case study in Bulu clinic on date of 8th February2017 until 18th February 2017. Collecting data with interview, observation and physical examination.Results: After do nursing action teach deep breathing relaxaation tecnique, give a health education and teaches gymnastic asthma for three time visits in one time 60 minute patient do not experience asthma relapse, the child is not coughing and healthy children.Conclusion: Teach deep breathing relaxation tecnique, give a helath education and gymnastic asthma could prevention asthma relapse in children.